Dimuridkan oleh Algoritma, Digembalakan oleh Media Sosial: (Sebuah Refleksi Kritis Peran Pendidikan Agama Kristen Dalam Keluarga) - Legi, Hendrik; Giban, Yoel; Kainara, Semi (Ambassadors: Jurnal Teologi dan Pendidikan Kristiani, 2025)
Abstract: The rapid development of digital technology has brought significant changes in the lifestyle of Christian families, especially in the process of child discipleship. Social media algorithms now play a dominant role in shaping children's behaviors, thoughts, and moral values, replacing the traditional role of the family as the center of faith education. This situation raises important questions. What is the role of Christian Religious Education (PAK) in the family in facing the challenges of algorithms and the dominance of social media in the process of forming children's faith? This research aims to critically reflect on the role of PAK in the Christian family in the context of an increasingly complex digital age. The research method used is a reflective qualitative approach with literature study and content analysis. The study found that many Christian families tend to let algorithms be the primary "disciples" of children, while parental spiritual involvement is diminishing. The novelty lies in an integrative perspective that links discipleship, digital algorithms, and the role of parents as spiritual shepherds of children in the contemporary context. This reflection emphasizes the importance of the family as the main space for faith education that must be active and conscious in shaping children's character through example, teaching the word, and managing digital media wisely. In conclusion, if the Christian family does not take back the mandate of discipleship from the hands of algorithms, then the world will continue to shepherd the younger generation with values that are contrary to the Gospel. Therefore, PAK in the family must be restored as the main strategy to form a resilient generation of disciples of Christ in the digital age.   Abstrak: Perkembangan teknologi digital yang pesat telah membawa perubahan signifikan dalam pola hidup keluarga Kristen, khususnya dalam proses pemuridan anak. Algoritma media sosial kini memainkan peran dominan dalam membentuk perilaku, pemikiran, dan nilai-nilai moral anak-anak, menggantikan peran tradisional keluarga sebagai pusat pendidikan iman. Situasi ini menimbulkan pertanyaan penting. Bagaimana peran Pendidikan Agama Kristen (PAK) dalam keluarga dalam menghadapi tantangan algoritma dan dominasi media sosial dalam proses pembentukan iman anak? Penelitian ini bertujuan untuk merefleksikan secara kritis peran PAK dalam keluarga Kristen dalam konteks era digital yang semakin kompleks. Metode penelitian yang digunakan adalah pendekatan kualitatif reflektif dengan studi literatur dan analisis isi. Penelitian ini menemukan bahwa banyak keluarga Kristen cenderung membiarkan algoritma menjadi “pemurid” utama anak, sementara keterlibatan spiritual orang tua semakin berkurang. Noveltinya terletak pada perspektif integratif yang mengaitkan pemuridan, algoritma digital, dan peran orang tua sebagai gembala rohani anak dalam konteks kekinian. Refleksi ini menekankan pentingnya keluarga sebagai ruang utama pendidikan iman yang harus aktif dan sadar membentuk karakter anak melalui keteladanan, pengajaran firman, dan pengelolaan media digital secara bijak. Kesimpulannya, jika keluarga Kristen tidak mengambil kembali mandat pemuridan dari tangan algoritma, maka dunia akan terus menggembalakan generasi muda dengan nilai-nilai yang bertentangan dengan Injil. Oleh sebab itu, PAK dalam keluarga harus dipulihkan sebagai strategi utama membentuk generasi murid Kristus yang tangguh di era digital